A PHYSIOTHERAPY STRATEGY IN SHOULDER ADHESIVE CAPSULITIS AFTER BREAST CANCER SURGERY: A CASE REPORT - Ulfa, Merinda; Sari, Dwi Rosella Komala; Purbasasana, P (Universitas Muhammadiyah Surakarta, 2021)
Background and Purpose: Breast cancer surgery may cause late effects of pain, range of motion loss, and activity limitation in the upper extremity (UE). The surgical complications was shoulder adhesive capsulitis (AC). AC is a condition of progressive loss of UE range of motion (ROM) and leading to limitations functional mobility. The purpose of this case report is to investigate the implementation of transcutaneous electrical nerve stimulation (TENS) combined with joint mobilization technique and hold relax technique for a patient with post mastectomy surgery and chemotherapy within a year with AC. Method: The patient was a 55-year-old female who was referred to physical therapy, Dr. Sardjito Central General Hospital. The patient had restricted mobility and pain in her left UE with a medical diagnosis of AC. A comprehensive physical treatments have done as well TENS, joint mobilization technique, and hold relax technique for twice a week. The outcomes were measured by goniometer, manual muscle testing (MMT), visual analog scale (VAS) and shoulder pain and disability index (SPADI). Result: The active ROM of shoulder increased significantly, decreased pain intensity (7/10 to 6/10) and increase muscle strength (3/5 to 4/5) and as well better functional performance (73.1% to 66.9%) in patient with AC affected by post mastectomy surgery. Conclusion: A good physiotherapy strategy for post mastectomy, clearly reduced impairments as muscle strength, joint mobility and functional activities of shoulder joint. As well this study could be a reference for clinicians to manage the patients with shoulder problem after breast cancer surgery.